2017
DOI: 10.1016/j.radonc.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intensity modulated radiation therapy dose painting for localized prostate cancer using 68 Ga-HBED-CC PSMA-PET/CT: A planning study based on histopathology reference

Abstract: IMRT dose painting using PSMA PET/CT was technically feasible and resulted in significantly higher TCPs without higher NTCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…A considerably higher TCP was found for the boost arm, for both IMPT and VMAT, compared to plans without boost. Similar results were also seen in the paper by Kuang et al [15] and Zamboglou et al [24] in the case of VMAT, using a different TCP model than ours. In our case, the large difference between the boost arms and non-boost arms might be due to the inclusion of tumour-index information together with ADC maps-based cell density, which increases the inter-patient tumour response differentiation, resulting in TCP curves with a larger range in D 50% across the cohort compared with those based on uniform cell densities [18].…”
Section: Discussionsupporting
confidence: 92%
“…A considerably higher TCP was found for the boost arm, for both IMPT and VMAT, compared to plans without boost. Similar results were also seen in the paper by Kuang et al [15] and Zamboglou et al [24] in the case of VMAT, using a different TCP model than ours. In our case, the large difference between the boost arms and non-boost arms might be due to the inclusion of tumour-index information together with ADC maps-based cell density, which increases the inter-patient tumour response differentiation, resulting in TCP curves with a larger range in D 50% across the cohort compared with those based on uniform cell densities [18].…”
Section: Discussionsupporting
confidence: 92%
“…8,9 Current advances in positron emission tomography (PET) imaging with the use of prostate-specific membrane antigen (PSMA)-PET/ computed tomography (CT) have been shown to be accurate in detecting segments containing intermediate-grade intraprostatic prostate cancer (International Society of Urological Pathology grade !2). 10 Studies have shown the feasibility of these techniques in DIL identification, 11 with ongoing studies investigating whether this additional information for radiation therapy planning is clinically meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…We could demonstrate that PSMA PET guided RT dose escalation considering the FLAME trial protocol [89] was feasible in ten of ten patients. Furthermore, TCP-histo was significant higher in the dose escalation arm compared to the conventionally fractionated arm (70% vs. 96%, p < 0.01) without increased risk of normal tissue toxicity [90].…”
Section: Psma Pet/ctmentioning
confidence: 89%